Antes do sim: rituais, celebrações e práticas de transição pré-nupciais - Simões, Juliana Fonseca (2007)
This work aimed at contributing for the understanding of the transition from premarital relationships to legal conjugality, identifying rituals, celebrations and practices implied in this change. It was based in semi-structured interviews with six young adults, three men and three women, already legally married, who previously cohabited for at least six months before their marriages. They were asked to mention the more significant events in their respective relationships, since the first days, and then induced to talk about those events, expanding the researcher s comprehension of their personal experience. The results showed that cohabitation was seen by the interviewed as a test drive , which helped them to get the certainty necessary for the decision to marry, without the seriousness of a formal union and emotional risks in case of failure. Regarding the couples families, although in thesis they did not approve this kind of union, for its lack of social acknowledgment, throughout time they tended to act as if the legal formalities were already met, demanding their sons to behave as legally married people. This contradiction did not appear in the case of the couples friends, which treated them accordingly since the beginning of co-habitation. Furthermore, and in accordance with the test drive idea, after making successfully the necessary adjustments the couples also tended to consider the marriage as the next step. The ceremony and marriage s party, as rituals in this transition, now become significant, as they symbolize the importance of this decision. Finally, for all these reasons - and some others related to gender, analyzed in this study - these pre- and post- marital practices oscillate between modern and the traditional models